Zmiany hormonalne u kobiet w wieku średnim a ich funkcjonowanie psychospołeczne = Hormonal changes in women of middle age and their psychosocial functioning - Jarecka, Karolina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The development of women in middle adulthood is associated with appropriate, for this period of life, hormonal changes leading to menopause. Menopause, although it is one of the natural and inevitable stages in a woman's life, is usually combined with aging and therefore assessed as an unfavorable "standard variant" - a period of many losses. Psychosocial factors: a sense of middle age crisis, unfavorable socio-cultural conditions of life and the negative attitude towards menopause seem to be as important a burden as hormonal factors, deciding on the course of the middle adulthood period and the intensity of menopausal symptoms.
Keywords: kobiety; średnia dorosłość; menopauza; zmiany hormonalne; zmiany psychospołeczne; women; middle adulthood; menopause; hormonal changes; psychosocial changes